ANALISA PENJADWALAN ULANG PEMBANGUNAN PROYEK WORK BOAT MENGGUNAKAN METODE PERT - Achmad Rifqi Nu’man; Fitri Hardiyanti; Gaguk Suhardjito (Proceeding Maritime Business Management Conference, 2023)
Ship transportation is the main support for the process of crossing between lands by water. One of the shipconstructions being carried out by PT. EMPAT SEKAWAN MARINE, namely the FRP work boat, wherethere was a delay in its completion, the project was planned to be completed in 30 days, but the company carried out the work to be completed within 37 days. The purpose of this study is to determine the durationand critical path in the network, and the probability of project completion. The method used is PERT. Theresearch results were obtained from the PERT method, namely the critical path in the network is found in the activities of the ship's hull (body), electrical systems, machining and steering systems, and safety equipment. The duration obtained from the PERT method is 34 days. The probability obtained at the client'srequest within a duration of 30 days, produces a probability value of 3.6% the possibility that the project can be completed on time and 96.4% the possibility that the project will be delayed. Calculation of the duration with the PERT method produces 34 days with a probability value of 50% the probability that the project can be completed and 50% the project will be postponed. Meanwhile, the company's work with a duration of 37 days produces a probability value of 90.9% probability that it can be completed and 9.1% possibility of project completion experiencing setbacks.